From AI to startup “Dreams”: How confidence and cost shape entrepreneurial intentions among accounting students - Lailatun Nafisa; Ach Maulidi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
This study examines how AI-related capabilities influence entrepreneurial intention through the role of entrepreneurial self-efficacy and cost mindfulness among accounting students. The study focuses on three dimensions of AI capability, including AI ambidexterity, AI literacy, and AI utilisation, to understand how these elements contribute to the development of perceived entrepreneurial ability. Data were collected from university students and analysed using SmartPLS to assess both measurement and structural models. Practically, we used questionnaires distributed to accounting students in a particular university. In terms of the research procedure, the data collection process was carried out through direct engagement with students. The findings show that AI ambidexterity, AI literacy, and AI utilisation have significant relationships with entrepreneurial self-efficacy, highlighting that different forms of capability contribute in complementary ways. Entrepreneurial self-efficacy is also found to have a significant effect on entrepreneurial intention and mediates the relationship between AI-related capabilities and intention. In contrast, cost mindfulness does not show a direct effect on entrepreneurial intention, although it plays a moderating role in shaping how self-efficacy translates into intention. These results suggest that entrepreneurial intention is formed through a process where capability is interpreted as confidence before influencing action. The study contributes to lietrature by offering a more integrated understanding of how technological capability, self-perception, and resource awareness interact in shaping entrepreneurial intention in a digital context.